Zasłużony najemnik w konstantynopolitańskim więzieniu Zagadkowa rola Haralda Hardrady w rewolcie 1042 roku - Lubik, Maciej (In Gremium. Studies in History, Culture and Politics, 2013)
A recognised mercenary in the Constantinopleprison. A mysterious role of Harald Hardrada in the revolt as of 1042 Harald Hardrada (about 1015-1066), the king of Norway, earlier the commander of Scandinavian mercenaries fighting for the Prince of Rus Yaroslav the Wise as well as for the Bizantine emperors (there as akoluthos – the commander of Varangian Guard) is a character whose history still raises doubts and leaves a lot of unanswered queries. It is due to all these inaccuracies of Scandinavian sources (mainly Heimskringla, Fagrskinny and Morkinskinny) as well as the absence of information concerning his deeds in the Rus and Bizantine’s sources (the only one who briefly mentions Harald is Kekaumenos, the author of the Advice for the Emperor). The greatest number of questions appear while considering the participation of Harald in a revolt against the Emperor Michael V, which took place in Constantinople in 1042. By confronting Synopsis of Histories by John Skylitzes, and The Chronicle by Michael Psellos with Scandinavian sources, one may conclude that Harald as the head of some Varangians supported the rebels and took active part in the Emperor’s overthrow. Nevertheless, this hypothesis is blurred by an essay written by Kekaumenos who knew Harald (not necessarily in person) and who does not mention any role of Harald at the times of these riots. Another vagueness concerns a short stay of Harald in prison. The Scandinavian sources claim that he was placed there by the successor of Michael V – Constantine IX. However, there is a justified hypothesis that it was Michael who arrested Harald on the charge of fraud of the Emperor’s wealth, even though if the hypothesis seem incorrect having analysed it deeply. Harald was probably preventively imprisoned by Constantine who urged to prevent possible cooperation of Harald and Yaroslav the Wise who planned to attack Constantinople.